Imaging of Pfeiffer Syndrome: A Case Report - Setiawan, Deni; Adibrata, Audy Sarah Putrini; Sari, Puspita P.; Kuntara, Atta; Yogaswara, Gery P. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Pfeiffer syndrome (PS) is a rare case in the Asian population, and only a few have been reported in Indonesia. This case report aims to spotlight the identification of PS with its correlated radiological imaging and distinguish it from other syndromes. CASE REPORTS: The authors report a case of a 5-year-old girl with PS, manifested by brachyturricephally, broad thumbs and big toes, and medially deviated big toes. The patient also had proptosis, midface hypoplasia, and bilateral Syndactyly of the fingers and toes. This report confirms the thorough examination procedures and indexes to identify PS as a literature reference for the research of reported PS in Southeast Asian race patients and as one comprehensive source for identification using index figures. CONCLUSION: This report provides a detailed radiology interpretation of PS on Southeast Asian race patients. Radiological findings can help in diagnosing and determining adequate treatment as needed.